PENGARUH KREDIBILITAS BRAND AMBASSADOR "EXO" DALAM IKLAN NATURE REPUBLIC TERHADAP PERILAKU KONSUMTIF(Survey Terhadap Followers Fanbase "EXO" di Sosial Media Instagram) - Risky Faradiba Ariyanti (2020)
Today, many companies are using artists as Brand Ambassadors to promote their products. produced by EXO as Nature Republic's Brand Ambassador (X) Credibility for Consumptive Behavior (Y). This study uses the Source Credibility Theory where this theory explains that the more credible the source, the easier it will be to affect the audience's perspective. In other words a person's credibility has an important role in persuading the audience to determine their views. The concepts used in this study include Marketing Communication, Advertising, Brand Ambassadors, Credibility, and Consumptive Behavior. The method used is quantitative by using random sampling and the target population is Instagram account followers @ exosmedia. In the correlation test in this study, there is a correlation between the two variables, but the value has a low relationship. Regression Test Results can be interpreted that the regression coefficient number obtained a positive value, it can be understood that the direction of the effect of variable X on variable Y is positive. The coefficient of determination of this study can be seen that the value of the coefficient of determination is 10% and the remaining 90% is influenced by other factors.